An impact of nanocrystals on dissolution rate of Lercanidipine: Supersaturation and crystallization by addition of solvent to antisolvent - Dolly Tulsibhai Gadhiya; Jayvadan K. Patel; Arti Arjanbhai Bagada (SpringerOpen, 2021)
Abstract Background Nanocrystals of any drug are pure solid drug particles with a mean diameter in nanometer range. Dissolution is a crucial factor for absorption of medicine in case of water-insoluble or poorly soluble drugs. The aim of this study was to develop nanocrystals of a hydrophobic drug, Lercanidipine, by addition of solvent to an antisolvent with high-speed homogenization to achieve dissolution and solubility enhancement. Addition of organic solvent to antisolvent results in genesis of nanosized particles due to fast nucleation process and rapid mixing. The nanosuspension was formulated using PVP K30 as a stabilizer. Further, nanosuspensions were lyophilized to convert into solid nanocrystals using mannitol as a cryoprotectant. The developed nanosuspensions were characterized for particle size, zeta potential, saturation solubility, and in vitro dissolution studies. Lyophilized solid nanocrystals were characterized for FTIR, SEM, XRD, and zeta potential (ζ). Results Central composite design was executed to study influence of amount of stabilizer and solvent to antisolvent ratio (independent variables) on particle size and % drug release at 10 min (dependent variables). The particle size of the developed Lercanidipine nanosuspensions were observed in the range of 302.00 ± 10.58 to 484.33 ± 6.51 nm measured by Zetatrac. A considerable increase was found in the solubility and dissolution rate of the nanocrystals as compared to pure drug. The drug release from Lercanidipine nanosuspensions was increased up to 88.95% within 10 min as compared to pure Lercanidipine which was only 21.53%. The X-ray diffraction study of lyophilized nanocrystals showed sharp and distinct peaks due to an increse in crystallinity of Lercanidipine Particle morphology was studied by scanning electron microscopy revealed that nanoprecipitated particles with lyophilization in the presence of mannitol exhibited dendrite needle-like crystals. Conclusion The nanocrystal development by antisolvent precipitation procedure using methanol as solvent, water as antisolvent, and low amounts of PVP K30 as stabilizer is a very promising and effective method to increase the dissolution rate of Lercanidipine. Graphical abstract